Penggunaan Bahasa Luwu - Indonesia di Sekolah Dasar - Fatimah. T (South Sulawesi Education Development, 2025)
This study aims to explore the effects of mixed language use among elementary school students. Utilizing a descriptive method and a qualitative approach, the research employed observation, interviews, and documentation as data collection instruments. The subjects of the study were fourth-grade students at SDN Buntu Sarek, Latimojong Subdistrict, Luwu Regency. The results revealed that the use of Luwu-Indonesian language among elementary school students exhibits complex dynamics. In formal learning interactions within the classroom, students tend to use Indonesian more frequently. Conversely, outside the classroom, Luwu dominates informal social interactions. This pattern reflects students' adaptation to various communication contexts, with environmental factors such as family, peers, and media playing significant roles in shaping their speech patterns. Families that actively use the Luwu language support the maintenance of cultural identity, while interactions with peers and media influence the use of Indonesian in informal settings. The use of mixed languages has positive impacts, enriching students' language skills by expanding their vocabulary through the ability to switch between Luwu and Indonesian. However, challenges arise in mastering either language deeply and in potential cultural identity conflicts due to exposure to formal Indonesian. Therefore, educational strategies that support understanding and developing language skills in both languages are necessary to address these challenges in Indonesian language learning at the elementary school level.